The biocompatibility of metal-organic framework coatings: an investigation on the stability of SURMOFs with regard to water and selected cell culture media - Hanke, Maximilian; Bauer, Stella; Christophis, Christof; Rosenhahn, Axel (Langmuir, 2012)
Highly porous thin ﬁlms based on a [Cu(bdc)2]n (bdc = benzene-1,4-dicarboxylic acid) metal−organic framework, MOF, grown using liquid-phase epitaxy (LPE) show remarkable stability in pure water as well as in artiﬁcial seawater. This opens the possibility to use these highly porous coatings for environmental and life science applications. Here we characterize in detail the stability of these SURMOF 2 thin ﬁlms under aqueous and cell culture conditions. We ﬁnd that the material degrades only very slowly in water and artiﬁcial seawater (ASW) whereas in typical cell culture media (PBS and DMEM) a rapid dissolution is observed. The release of Cu2+ ions resulting from the dissolution of the SURMOF 2 in the liquids exhibits no adverse eﬀect on the adhesion of ﬁbroblasts, prototype eukaryotic cells, to the substrate and their subsequent proliferation, thus demonstrating the biocompatibility of SURMOF 2 surface coatings. Thus, the results are an important step toward application of these porous materials as a slow release matrix, for example, for pharmaceuticals and growth factors.